Neural correlates of subjective CS/UCS association in appetitive conditioning. Issue 4 (3rd January 2018) - Tapia León, Isabell; Kruse, Onno; Stalder, Tobias; Stark, Rudolf; Klucken, Tim
Abstract: Explicit knowledge of conditioned stimulus (CS)/unconditioned stimulus (UCS) associations is proposed as important factor in classical conditioning. However, while previous studies have focused on its roles in fear conditioning, it has been neglected in the context of appetitive conditioning. The present functional magnetic resonance study aimed to investigate neural activation and functional connectivity linked to subjective CS/UCS association in appetitive conditioning. In total, 85 subjects participated in an appetitive acquisition procedure in which a neutral stimulus (CS+) was paired with a monetary reward, while another neutral stimulus (CS‐) was never paired with the reward. Directly afterwards, subjective CS/UCS association was assessed by measuring the extent to which the CS+ was thought to be associated with the UCS compared to the CS‐. Close relationships were established between subjective CS/UCS association and activations in the primary visual cortex (V1) during the early phase of conditioning and in the striatum during the late conditioning phase. In addition, we observed inverse relationships between subjective CS/UCS association and both V1/ventromedial prefrontal cortex (vmPFC) and striatal/vmPFC connectivity. The results suggest the involvement of decoupling vmPFC connectivity in reward learning in general and the roles of attentional processes in the formation of the subjective CS/UCS association during the early phase and reward prediction during the late phase of appetitive conditioning.